Benthic Macroinvertebrate Composition and Diversity in The Madek River, Kluang, Johor, Malaysia. - Aweng Eh Rak; Ismid Said; Maketab Mohamed; Ahmad Abas; Chow, V.K.K (2010)
Benthic Macroinvertebrates, or more simply “benthos”, are animals without backbones that are larger than ½ millimeter. The identification of benthic population and assemblages can be uses as biological to assess the water quality. The index parametes can be useful for assessing the fishery potentials, interaction and intertidal ecologies. The study area is situated in Kluang, Johor, Malaysia. The sampling station is located at the Madek river which flows through a logging area in the Kluang Forest Reserve. The sampling was conducted four (4) times within November 2008 to August 2009. Surber Net measuring 500 micron mesh size combined with a rectangular quadrate of 30cm x 30cm (0.09 m2) were used to macroinvertebrates. Each station comprised of three sampling points for macroinvertebrate sampling; with one situated at the right bank, one in the middle of the river and the third sampling point is located at the left bank. All three sample from each sampling station were composited as one sample. Biodiversity indices was analyzed using the Species Diversity and Richness software developed by Henderson, P. A. from University of Oxford, department of zoology and RMH Seaby PISCES Conversation Limited. For water quality, at each station, six in-situ parameters were measured following the standard procedure of U.S Environmental Protection Agency. The parameter probe Model YSI 6920 with 650 MDS Display/Logger as well as a single parameter probe. A total of 57 genus were identified from the upstream station, where 53 genus were classified as Insecta and 4 genus as Malacostra. Meanwhile, a total 47 were identified from the downstream station, where 39 genus were classified as Insecta and 6 genus as Malacostraca and 2 genus as Gastropoda. The monthly variations of population density, species diversity, richness, evenness, dominance on benthic macroinvertebrate assemblage and river water quality were investigated within November 2008 to August 2009.